Oligomer-salt derived 3D, heavily nitrogen doped, porous carbon for Li-ion hybrid electrochemical capacitors application - Gokhale, Rohan; Aravindan, Vanchiappan; Yadav, Prasad; Jain, Srashti; Phase, Deodatta; Madhavi, Srinivasan; Ogale, Satishchandra (Carbon, 2014)
3D high surface area porous carbon is seen to form via self assembly of porous graphene sheets by direct pyrolysis of an oligomer salt tailored for the realization of molecular level activation. The oligomer salt was derived from 4-amino benzoic acid as the monomer by a facile free radical polymerization process. Incorporation of the functional groups (-COONa) eliminate the need for any external activating agents (KOH, ZnCl2, etc.) and also render high degree of sub-nanoscale homogeneity. This oligomer derived carbon (ODC) exhibits efficient performance in non-aqueous charge storage application namely Li-ion hybrid electrochemical capacitor (Li-HEC) owing to its high surface area, 3D interconnectivity and an appropriate pore size distribution. The Li-HEC fabricated with ODC based electrodes delivered a maximum energy density of similar to 63 Wh kg(-1) with spinel L4Ti5O12 as the anode. (C) 2014 Elsevier Ltd. All rights reserved.

Direct Z-scheme g-C3N4/FeWO4 nanocomposite for enhanced and selective photocatalytic CO2 reduction under visible light - Bhosale, Reshma; Jain, Srashti; Vinod, Chathakudath Prabhakaran; Kumar, Santosh; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2019)
Photocatalytic reduction of CO2 to renewable solar fuels is considered to be a promising strategy to simultaneously solve both global warming and energy crises. However, development of a superior photocatalytic system with high product selectivity for CO2 reduction under solar light is the prime requisite. Herein, a series of nature-inspired Z-scheme g C3N4/FeWO4 composites are prepared for higher performance and selective CO2 reduction to CO as solar fuel under solar light. The novel direct Z-scheme coupling of the visible light-active FeWO4 nanoparticles with C3N4 nanosheets is seen to exhibit excellent performance for CO production with a rate of 6 mu mol/g/h at an ambient temperature, almost 6 times higher compared to pristine C3N4 and 15 times higher than pristine FeWO4. More importantly, selectivity for CO is 100% over other carbon products from CO, reduction and more than 90% over. H-2 products from water splitting. Our results clearly demonstrate that the staggered band structure between FeWO4 and C3N4 reflecting the nature-inspired Z-scheme system not only favors superior spatial separation of the electron hole pair in g-C3N4/FeWO4 but also shows good reusability. The present work provides unprecedented insights for constructing the direct Z-scheme by mimicking the nature for high performance and selective photocatalytic CO2 reduction into solar fuels under solar light.
Keywords: C3N4; CO2 reduction; FeWO4; Photocatalysis; solar fuels; Z-scheme